Self-efficacy, habit strength, health locus of control and response to the personalised nutrition Food4Me intervention study - Stewart Knox, BJ (2022)
PurposeRandomised controlled trials identify causal links between variables but not why an outcome has occurred. This analysis sought to determine how psychological factors assessed at baseline influenced response to personalised nutrition. Design/methodology/approachWeb-based, randomised, controlled trial (RCT) was conducted across seven European countries. Volunteers, both male and female, aged over 18 years were randomised to either a non-personalised (control) or a personalised (treatment) dietary advice condition. Linear mixed model analysis with fixed effects was used to compare associations between internal and external health locus of control (HLoC), nutrition self-efficacy (NS-E) and self-report habit index (S-RHI) at baseline (N = 1444), with healthy eating index (HEI) and Mediterranean diet index (MDI) scores between conditions post-intervention (N = 763). FindingsAn increase in MDI scores was observed between baseline and six months in the treatment group which was associated with higher NS-E (p < 0.001), S-RHI (p < 0.001) and external HLoC (p < 0.001). Increase in HEI between baseline and six months in the treatment group was associated with higher NS-E (p < 0.001) and external HLoC (p = 0.009). Interaction between time and condition indicated increased HEI scores (p < 0.001), which were associated with higher S-RHI scores in the treatment than control group (p = 0.032). Internal HLoC had no effect on MDI or HEI. Originality/valuePsychological factors associated with behaviour change need consideration when tailoring dietary advice. Those with weaker habit strength will require communication focussed upon establishing dietary habits and support in integrating advised changes into daily routine. Information on habit strength can also be used to inform how progress towards dietary goals is monitored and fed back to the individual. Those with stronger habit strength are more likely to benefit from personalised nutrition.